PENGEMBANGAN APLIKASI THERA UNTUK MENINGKATAKAN KETERAMPILAN MEMBACA DAN KARAKTER CINTA BUDAYA LOKAL - Tri Yuli Setyoningrum (Jurnal Guru Dikmen dan Diksus, 2022)
The purpose of this research and development THERA application is to improve English reading skills and introducing local culture for character building THERA application is designed for smartphones with android specifications. Specifications THERA application requires 32.62 MB of storage space and 340 KB of data. THERA application can be used both online and offline. This research was conducted at SMA Negeri 1 Blora class X MIPA with 108 students. This study measures the validity, practicality, and effectiveness of THERA educational game learning media to improve reading skills and enhance the character of loving local culture. The Research and Development method used is the Sugiyono and Dick & Carey development model. The flow of the research development model is: potential and problems, collection, product development, validation, revision, product testing, product revision and usage testing. The application has been validated by material experts and media experts and shows excellent results. Likewise, the results of using applications for learning English through tests also increased significantly. Students' attitudes towards local culture are measured using indicators of interest, loyalty, concern and appreciation. The results have increased significantly. It can be concluded that the THERA application in learning English improves reading skills and character of love for local culture. This is in accordance with the characteristics of students who like games.